ANALISIS EKSISTENSI HUKUM ADAT AKIBAT PERKEMBANGAN PERATURAN DAERAH DI BIDANG INDUSTRI PARIWISATA (Studi Sosio-Legal Masyarakat Adat â€œWetu Teluâ€ di Bayan, Lombok Utara) - Irham Rahman; Rizki Yudha Bramantyo (Fakultas Hukum Universitas Islam Malang, 2021)
The existence of indigenous peoples has been recognized and respected by the Constitution. The Wetu Telu indigenous people have traditions from their ancestors with Islamic nuances and their existence is recognized until now. Besides, the local government's strategy to develop the tourism sector to improve the economy and regional development which is designed in regional regulations can affect the existence of Indigenous people. The purpose of this research is to know the changes in the existence of the Wetu Telu community customary law and to know the implementation of Regional Regulations in the tourism sector in Bayan village, North Lombok Regency, West Nusa Tenggara. This research uses juridical empirical or socio-legal research, which is a type of sociological legal research or field research that examines applicable legal provisions. Cultural preservation and tourism development need a Regional Regulation on the Recognition and Protection of Indigenous Peoples to protect normatively and with legal certainty and harmonize Regional Regulations between tourism development and recognition of indigenous peoples.